Pengaruh Tingkat Inflasi Dan Suku Bunga Terhadap Beta Saham Pada Perusahaan Real Estate Di Bursa Efek Indonesia - Catur Kumala Dewi (RJABM (Research Journal of Accounting and Business Management), 2017)
The interest rate affects the stock price at which the rising stock price will affect the stock return. If interest rates rise, that will lead to interest rates on loan which will affect the creditor or company. Companies which have high risk of interest rate will affect the price of their shares because investors mark that company has no good prospects. It is important to involve external factors to make the research more accurate. External factors include inflation rate, gross domestic product, interest rate and exchange rate. The exchange rate could be affected by inflation. Fluctuations of exchange rate may result the changes in the company's cash flow in the future. The risk caused by this fluctuation is the higher the fluctuation; the greater the risk received otherwise the lower the fluctuation, the lower the risk. This risk will affect the stock returns.